Bipolar Disorder in Turkey - Bulent Kadri Gultekin; Sermin Kesebir; Lut Tamam (Psikiyatride Güncel Yaklaşımlar, 2014)
Assessment of studies related with bipolar disorder in Turkey did not reveal an epidemiologically qualified field study. Most of the studies are hospital based or clinical studies which did not include a systematical scanning and did not aim to collect any epidemiological data and transfer information to health authorities. The generalizability of these studies to our community is far from being valid and reliable. On the other hand, a profile which will be created by reviewing the findings of these studies performed in various regions of Turkey will have a contribution to knowing the and ldquo;unique to us and rdquo; features of bipolar disorder and determining cultural risk factors. All this information can constitute a basis for formation and development of public mental health services related with bipolar disorder. In Turkey, the need for epidemiologically significant, polycentric, public sampled studies with broad participation is indispensable. Although our psychiatric epidemiology and clinical studies include necessary scientific basis, they are not powerful enough to evaluate the authentic and progressional relations such as rapid urbanization and immigration. The aim of this review is to evaluate and discuss prominent epidemiological findings, deficiencies and possibile future activities related with studies conducted in Turkey about bipolar disorder.. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2014; 6(2.000): 199-209]